The Self-Assembly Phenomenon of Poloxamers and Its Effect on the Dissolution of a Poorly Soluble Drug from Solid Dispersions Obtained by Solvent Methods - Joanna Szafraniec (Pharmaceutics, 2019)
The self-assembly phenomenon of amphiphiles has attracted particular attention in recent years due to its wide range of applications. The formation of nanoassemblies able to solubilize sparingly water-soluble drugs was found to be a strategy to solve the problem of poor solubility of active pharmaceutical ingredients. Binary and ternary solid dispersions containing Biopharmaceutics Classification System (BCS) class II drug bicalutamide and either Poloxamer®188 or Poloxamer®407 as the surface active agents were obtained by either spray drying or solvent evaporation under reduced pressure. Both processes led to morphological changes and a reduction of particle size, as confirmed by scanning electron microscopy and laser diffraction measurements. The increase in powder wettability was confirmed by means of contact angle measurements. The effect of an alteration of the crystal structure was followed by powder X-ray diffractometry while thermal properties were determined using differential scanning calorimetry. Interestingly, bicalutamide exhibited a polymorph transition after spray drying with the poloxamer and polyvinylpyrrolidone (PVP), while the poloxamer underwent partial amorphization. Moreover, due to the surface activity of the carrier, the solid dispersions formed nanoaggregates in water, as confirmed using dynamic light scattering measurements. The aggregates measuring 200–300 nm in diameter were able to solubilize bicalutamide inside the hydrophobic inner parts. The self-assembly of binary systems was found to improve the amount of dissolved bicalutamide by 4- to 8-fold in comparison to untreated drug. The improvement in drug dissolution was correlated with the solubilization of poorly soluble molecules by macromolecules, as assessed using emission spectroscopy.